Az apaszerep funkciói és az engedelmesség foka a kora újkori államelméletekben - Rigó, Balázs (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2024)
In the early modern theories of the state, thinking about governance started from the idea of body politic, through the introduction of passions and the family, to the patriarchal theory of the state, in which the monarch governs the people as a family as head of the family. To the head of the family, like to the monarch, the members of the family, like the people, owe obedience according to the laws of nature. The family has become the interpretative framework for the description of society, in which the monarch, by right of his supremacy, has been transformed into the head of the family. At the same time, the concept of the head of the family has undergone a significant change. The change in the role of the father has been accompanied by a change in the content of obedience as well.